The Analysis of GCP Correction Toward GNSS-PPK for LandRegistration Base-map in Muktisari Village, Cipaku District, Ciamis Regency - Niswah Selmi Kaffa; Regita Faridatunisa Wijayanti; Taufik Kusetiyohadi; Hesekiel Sijabat; Tedy Pranadiarso; Hilma Wasilah Robbani; Gholiqul Amrodh Alawy (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
The Comprehensive Systematic Land Registration Program (PTSL) main requirement is land registration map in a scale of 1:1000 and horizontal accuracy (CE90) class 1 of 0,3 meters. Global Navigation Satellite System–Post Processing Kinematic (GNSS-PPK) provides good accuracy without Ground Control Point (GCP) correction, thus reducing cost and data acquisition time. GNSS-PPK without GCP correction is considered accurate in areas <500 meters elevation. This research aims to determine the GCP correction importance for photo accuracy in PPK process. This study analyzes aerial photo accuracy with and without GCP correction in areas with elevations from 200 to 430 meters. The data required are aerial photos, coordinates in RINEX files, Digital Terrain Model (DTM), and 8 GCP points. Coordinate files are calculated using the PPK method then used for photo correction. Photos are processed with and without GCP correction. Photo without GCP correction has a significant deviation than photo with GCP correction and does not meet the CE90 requirements. The accuracy has a negative correlation with an elevation of -0,041 without GCP and -0,76 with GCP. This study proves that GNSS-PPK method still requires GCP and it is not proven deviation in data without the GCP correction is directly proportional to elevation.